P741 Very high rate of tuberculosis complicating infliximab therapy for inflammatory bowel disease despite tuberculosis screening in India. (16th January 2018) - Agarwal, A; Kedia, S; Jain, S; Gupta, V; Bopanna, S; Yadav, D; Goyal, S; Venegella, P M; Makharia, G; Ahuja, V
Abstract: Background: With the increasing disease burden of inflammatory bowel disease (IBD), the use of infliximab (IFX) is increasing in India. The data on the risk of tuberculosis (TB) reactivation with infliximab in countries endemic for TB, like India, is limited. The present study assessed the risk of TB reactivation on IFX and its predictors in Indian IBD patients. Methods: A retrospective review of consecutive patients with IBD who received IFX, and were on follow-up from January 2005 to November 2017 was done. The data were recorded on age/disease duration at which IFX was started, indication for IFX, response to IFX, the incidence of TB after IFX, duration at which TB developed and type of TB (pulmonary (PTB)/extra-pulmonary (EPTB)/disseminated). Results: Sixty-nine patients [(22 ulcerative colitis (UC)/47 Crohn's disease (CD)] were included (mean age: 36 + 14 years, 50.7% males). Median follow-up duration after IFX was 19 (IQR: 5.5–48.7) months. Primary non-response at 8 weeks and secondary loss of response at 26 and 52 weeks were seen in 14.5%, 6% and 31% patients, respectively. Prior to IFX, all patients were screened for latent tuberculosis (LTB). Eight (11.59%) patients developed TB (disseminated: 62.5%, EPTB: 25%, PTB: 12.5%) after a median of 19 weeks (IQR: 14–84.5) of IFX; none had evidence of LTB on screening. Of 8 patients who developed TB, 7 patients had undergone contrast-enhanced chest tomography as an additional precautionary screening investigation for LTB. Though not statistically significant, more patients with CD than UC (14.9% vs. 4.5%, p = 0.21), and more patients with past history of TB (25% vs. 9.8%, p = 0.21), developed TB after IFX. Among patients with CD, no patient with penetrating or perianal disease developed TB. No other baseline factor including age, gender, disease duration, or presence of extra-intestinal manifestations could predict the development of TB. Conclusions: There is an extremely high rate of TB with IFX in Indian patients with IBD. Current screening techniques are ineffective and it is difficult to predict TB after IFX treatment. Further research is required to develop predictors of TB in patients on biologicals.